To study the correlation between red cell distribution width and left ventricular ejection fraction in patients of acute myocardial infraction - Sharma, Ramji; Mohammed, Akram; Shrivastava, Mayank; Mathur, Ajay (International Journal of Research in Medical Sciences, 2017)
Background: Ischemic heart disease (IHD) is a condition in which there is an inadequate supply of blood and oxygen to a portion of myocardium. The objective of study was to assess the correlation between red cell distribution width and left ventricular ejection fraction in patients presenting with acute myocardial infarction. Methods: Study was conducted on 200 patients admitted at tertiary care centre with acute myocardial infarction satisfying inclusion criteria. Detailed history and clinical examination was done. RDW and other CBC parameters were calculated by an automatic blood counter and measurement of LVEF done by 2D-echocardiography. Results: Out of 200 patients of acute myocardial infarction 178 (89%) were male and 22 (11%) were female. Both RDW and LVEF are linked in patients of acute myocardial infarctions, as there was statistically significant correlation between high RDW and low LVEF (P <0.01, r - value 0.432). Conclusions: It is observed that increase RDW and decrease LVEF were linked together which is statistically significant. RDW can be used to assess severity and outcome in patients of acute myocardial infraction on their initial presentation especially at peripheral health centre where echocardiography is not available routinely.